Molecular and functional characterization of Hv1 proton channel in human granulocytes. - Gábor L Petheo (Public Library of Science (PLoS), 2010)
Voltage-gated proton current (I(Hv)) has been characterized in several cell types, but the majority of the data was collected in phagocytes, especially in human granulocytes. The prevailing view about the role of I(Hv) in phagocytes is that it is an essential supporter of the intense and sustained activity of Nox2 (the core enzyme of the phagocyte NADPH oxidase complex) during respiratory burst. Recently H(v)1, a voltage-gated proton channel, was cloned, and leukocytes from H(v)1 knockout mice display impaired respiratory burst. On the other hand, hardly anything is known about H(v)1 in human granulocytes. Using qPCR and a self made antibody, we detected a significant amount of H(v)1 in human eosinophil and neutrophil granulocytes and in PLB-985 leukemia cells. Using different crosslinking agents and detergents in reducing and non-reducing PAGE, significant expression of H(v)1 homodimers, but not that of higher-order multimers, could be detected in granulocytes. Results of subcellular fractionation and confocal imaging indicate that H(v)1 is resident in both plasmalemmal and granular membrane compartments of resting neutrophils. Furthermore, it is also demonstrated that H(v)1 accumulates in phagosome wall during zymosan engulfment together with, but independently of Nox2. During granulocytic differentiation early and parallel upregulation of H(v)1 and Nox2 expression was observed in PLB-985 cells. The upregulation of H(v)1 or Nox2 expression did not require the normal expression of the other molecule. Using RNA interference, we obtained strong correlation between H(v)1 expression and I(Hv) density in PLB-985 cells. It is also demonstrated that a massive reduction in H(v)1 expression can limit the Nox2 mediated superoxide production of PLB-985 granulocytes. In summary, beside monomers native H(v)1 forms stable proton channel dimer in resting and activated human granulocytes. The expression pattern of H(v)1 in granulocytes is optimized to support intense NADPH oxidase activity.